PERENCANAAN PEMBANGUNAN OBYEK WISATA (Studi di Dinas Pariwisata Kabupaten Halmahera Barat) - DJODJOBO, FENESIA; LENGKONG, FLORENCE DAICY; RURU, JOORIE MARHAEN (Sam Ratulangi University, 2017)
Abstract: This study aims to find out how the planning of tourism object development conducted by the Tourism Department.The research was conducted in April-June 2017. The method used in this research is qualitative with the source data is unsorman and non human element.From the results of the study explained that the Department of Tourism Halmahera West, in the planning is done very well, canbe seen in the Strategic Plan (RENSTRA) Tourism Department.With reference to some of the interviews in this study, it is deemed necessary to provide some suggestions as a solution to problemsolving in this study, as follows. (B), it is necessary to have commitment and joint efforts from related institution to advancetourism sector, in order to support West Halmahera development programKeywords: Tourism Development Planning